The clinical usefulness of assessing the concentration of cell adhesion molecules sVCAM-1 and sICAM-1 in the serum of women with primary breast cancer - Thielemann, Anna; Baszczuk, Aleksandra; Kopczyński, Zygmunt; Nowak, Adrianna; Grodecka-Gazdecka, Sylwia (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study: Assessment of the concentrations of the soluble forms of the cell adhesion molecules sVCAM-1 and sICAM-1 in serum of female breast cancer patients. These concentrations were assessed in relation to factors such as: age, clinical stage of disease, histological grade of malignancy, the status of the local axillary lymph nodes, and the size of the primary tumour. Material and methods: A total of 103 patients with primary breast cancer, aged 29 to 89 years, were investigated. The control group consisted of 40 healthy women. The concentration of sVCAM-1 and sICAM-1 was assessed using an enzyme-linked immunosorbent assay (ELISA). Results: The results of the study suggest that the level of sVCAM-1 and sICAM-1 in the serum of women with breast cancer was significantly higher than that seen in the serum of healthy women. A relationship between the level of adhesion molecules and the stage of clinical disease advancement was discovered. There was a correlation between the increasing concentrations of sVCAM-1 and sICAM-1 and with the aggressiveness of the disease. Significant differences were also found in the group of women with metastases to the axillary lymph nodes and women with no metastasis. Similar correlations were found between sVCAM-1 and sICAM-1 levels and the size of primary tumour. Conclusions : The results obtained suggest that the assessment of the soluble forms of sVCAM-1 and sICAM-1 may be useful indicators in the assessment of the clinical advancement of breast cancer.